Marketing implant dentistry : attract and influence patients to accept your dental implant treatment plan - Hines, Marcus (Hoboken, New Jersey : John Wiley and Sons, Inc., 2015)
A large percentage of skilled dental professionals lack the tools and comfort level required to market themselves and their dental implant practices effectively As a consequence, these dental professionals miss several opportunities to help patients and grow their business. Even those who recognize the need for marketing often don't have the experience or training to do so effectively. Marketing Implant Dentistry meets this need by giving dentists the tools to better market and promote their practices and to gain case acceptance.Marketing Implant Dentistry presents proven approaches for attr.
Visual aids and verbal skills -- Patient education seminars -- Partnering with physicians for dental implants -- Marketing full-arch implant dentistry in your practice -- Implant marketing for the surgical specialist -- Database marketing -- Internet presence.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Dental Implants; Dental implants -- Methods; Dental implants -- economics; MEDICAL / Surgery / General; Dental implantation -- Economics; Marketing of health services -- Methods; Medicine; Dental Implantation -- economics; Marketing of Health Services -- methods; Audiovisual Aids -- standards; Dental Implants -- economics; Internet -- standards; Electronic books; Electronic books